In Vivo and in Silico Assessment of Ameliorative Effects of Xylopia aethiopica on Testosterone Propionate-Induced Benign Prostatic Hyperplasia - Udu A. Ibiam; Daniel E. Uti; Chris C. Ejeogo; Obasi U. Orji; Patrick M. Aja; Ezeaani N. Nwamaka; Esther U. Alum; Chukwuma Chukwu; Chinyere Aloke; Kate E. Chinedum; Peter Agu; Valentine Nwobodo (Pharmaceutical Fronts, 2023)
Xylopia aethiopica (XAE) is a commonly used herbal medicine and contains rich active ingredients for a variety of biological activities. The study aimed to explore the role of XAE in the management of benign prostatic hyperplasia (BPH). In the study, testosterone propionate-induced BPH in albino rats was established and treated with different concentrations of ethanol extract of XAE leaf. After treatment, the rats were sacrificed, and the body and prostate weights were recorded. The prostate-specific antigen (PSA) and acid phosphatase (ACP) levels in the blood samples were also determined. Gas chromatography-mass spectrometry was conducted to assess the active chemical compounds. Docking analysis was performed to screen chemical compounds by evaluating their binding affinity with two pro-BPH protein targets (cellular prostatic ACP and PSA). Our data showed the presence of 44 chemical compounds in XAE leaf extract. The body and prostate weights, as well as the levels of PSA and ACP, were significantly increased in BPH induction, and the changing trend was significantly reversed by additional XAE treatment. Interestingly, PSA and ACP levels in XAE-treated groups were reduced to almost the same levels as those in the healthy control. Docking analysis identified four top-posed compounds: β-amyrin, α-amyrin, α-amyrenone, and lupenone with stronger binding energies to prostatic ACP being −9.8, −8.3, −8.4, and −8.6, respectively, compared with the standard drug finasteride (−8.3). Furthermore, the two-dimensional analysis revealed strong interactions through hydrogen bonding, covalent interactions, and several van der Waal forces between the lead compounds and the target proteins. Notably, there was a recurrence interaction between similar residues Asn-1062, Lys-1250, Lys-1059, and Phe-1060 on the protein targets and the lead compounds. The study first revealed the role of XAE in BPH therapy and will help in drug design based on the lead compounds discovered in this work.